Unpacking vulnerability through an intersectional lens in Myanmar - International Water Management Institute (2021)
The Gulf of Mottama in southern Myanmar, is a challenging place to live for some of the most marginalized rural communities. Rapid erosion, landslides and soil salinization caused by strong inter-tidal shifts present risks to both human safety and livelihoods. Climate change exacerbates these challenges particularly for those whose capacity to adapt is co-determined by disparities by ethnicity, race, and gender. These intersectional inequalities that create very different adaptive capacities amongst different households and individuals make clear that external support for climate adaptation need to avoid one size fits all strategies, but rather must be flexible to address the needs of specific marginalized groups. In this documentary, we capture memories, lived experiences and images from the ground through participatory storytelling to illustrate the most vulnerable may be left behind.